Multiphysics modeling of arching effects in fill mass. (March 2017) - Cui, Liang; Fall, Mamadou
Abstract: A numerical modeling study is conducted to assess and gain a better understanding of the arching effects of field cemented tailings backfill (CTB). An integrated multiphysics model is developed that can illustrate and capture the changes in the material properties of CTB, consolidation behavior of CTB mass, and the shear behavior at the CTB/Rockwall interface. The predictive capability of the model has been successfully verified with comparisons of the predicted results with monitoring data taken from a series of field studies. The model is then used to simulate a series of applications that are relevant to CTB in practice.